Aplicación del juego y su incidencia en el desarrollo del lenguaje oral de los niños y niñas del primer año de educación general básica de la “Unidad Educativa Municipal Borja” de la ciudad de Loja. Periodo lectivo 2014-2015 - Chamba Quiñonez, Rosa Marianela (2016)
This paper is titled: APPLICATION OF THE GAME AND ITS IMPACT ON THE DEVELOPMENT OF ORAL LANGUAGE CHILDREN FIRST YEAR OF BASIC EDUCATION GENERAL "EDUCATIONAL UNIT MUNICIPAL BORJA" CITY OF LOJA school period 2014-2015. The research has as its central problem: the impact of the games on the development of oral language in children / as the first year of Basic Education, Borja Municipal Education Unit of the city of Loja. 2014- 2015 period. The overall objective is to educate teachers ranging from pre through research, the importance of using games and their impact on the development of oral language of children of the first year of basic general education "Education Unit Municipal Borja "from the city of Loja The methods used in this work are: a scientist who helped describe the internal relations, deductive allowed the delimitation of the problem, inductive allowed to obtain valid, descriptive findings helped to understand the data, statistical allowed to use descriptive statistics and analytical - synthetic It served to analyze, organize, process, interpret and synthesize information obtained in fieldwork. Depending on the activities applied to children in the first year of basic identified that 14% their learning was very satisfactory 55% satisfactory and 30% moderately satisfactory, which indicates that you must work hard on this aspect of language learning oral. The recommendations are addressed to the authorities of the educational institution involved in the problem to worry about the teachers ensure the appropriate physical environment for the organization of the games. On the other hand, the teacher is recommended that the organization of the games learning experiences to insert chords aspects that make up the oral language, and directed to the group needs more.